Elongated styloid process in a dry human skull and its relation to the Eagle’s Syndrome: case report and biometrical assessment (Research, Society and Development, 2020)
The purpose of the present study was to report a case of an elongated styloid process in a dry human skull and present its biometrical values. The styloid processes of the skull from an 80-year-old Brazilian female individual were inspected and 10 measures were performed bilaterally. Despite small differences between the right and left styloid processes regarding the antero-posterior and lateral-medial widths on the three thirds measured, one must highlight the considerable differences showed on the total length of the styloid process (left side: 65.94; right side: 28.90) and on the length of the sheath of the styloid process, which was of 30.01mm on the left side and it was not acquired on the right side because of its small dimensions.  The paper discusses its findings from an anatomical and clinical perspectives, providing anatomical basis for a better understanding of the Eagle’s syndrome.